Enterococcus faecalis OG1RF:pMV158 survives and proliferates in the house fly digestive tract. - Doud, C. W.; Zurek, Ludek (My University, 2012)
Enterococcus faecalis is an important nosocomial pathogen and house flies have been implicated in the dissemination of this bacterium. In this study, GFP-expressing E. faecalis OG1RF:pMV158 was used to track the fate of the bacterium in the digestive tract of the house fly, Musca domestica (L.) to assess the vector potential of this insect for E. faecalis. Colony forming unit (CFU) counts were obtained from viable fluorescing E. faecalis recovered from mouthparts and digestive tract regions (labelum, foregut, midgut, and hindgut) at 1, 4, 8, 24, 48, 72, and 96 h after the bacterial exposure. Bacterial counts were significantly highest in the midgut at 1 h and 4 h and declined during the first 24 h. In the labelum, E. faecalis concentrations were low within the first 24 h and then greatly increased. Bacterial counts and direct observations of the digestive tract under a dissecting microscope with ultra violet light revealed that E. faecalis peaked in the crop after 48 h and remained high until the end of the experiment. Concentrations of E. faecalis in the hindgut were low when compared with other parts of the digestive tract. Microscopy and CFU counts suggest that E. faecalis was digested in the midgut but proliferated in the crop. Both drinking water and feed (flaked corn) sampled at the end of the assay (96 h) were contaminated by fluorescing E. faecalis, demonstrating that the flies disseminated E. faecalis. Our data support the notion that house flies can act as a bioenhanced vector for bacteria.
Citation: Doud, C. W., and L. Zurek. (2012). Enterococcus Faecalis OG1RF:PMV158 Survives and Proliferates in the House Fly Digestive Tract. Journal of Medical Entomology 49 (1): 150–55. https://doi.org/10.1603/ME11167.
Keywords: Musca domestica; Enterococci; Digestive tract; Proliferation; Crop